A cutting mechanics model of constant cross-section type disc cutter and its application based on dense core theory. (February 2022) - She, Lei; Zhang, She-rong; Wang, Chao; Du, Min; Yang, Peng
Abstract: The rock-cutting mechanism and force prediction model of disc cutter considering the effect of dense core are proposed in this study. According to the working characteristics of disc cutter and rock breakage theory, the contribution of dense core in the complex process of rock-cutting by disc cutter is investigated in detail. Based on the Mohr-Coulomb failure criterion of the rock, a theoretical analytical expression of dense core length is derived, and a cutting mechanics model of constant cross-section (CCS) type disc cutter is established; thus, the quantitative relationship between normal force and rolling force of a disc cutter and rock mechanical characteristics, cutter geometric parameters and cutting parameters is obtained. This model incorporates the size of a dense core. A rich full-scale linear cutting machine (LCM) database is developed from the literature and the theoretical force is compared with the experimental force. The results show that the proposed theoretical model can accurately predict 93% of the average disc cutter force acting on the rock uniaxial compressive strength (UCS) ranging from 8.4 to 355.6 MPa. As the rock UCS increases, the model prediction ability is significantly improved. In addition, the results comparison and performance evaluation between the proposed model and existing classical models prove that the proposed model is reasonable and reliable. Finally, the effects of model parameters (penetration, rock compressive strength, cohesion, internal friction angle and blade angle) on forces and efficiency of rock-cutting by disc cutter are also discussed. The results illustrate that the rock breakage regularity of disc cutter obtained based on theoretical model is consistent with that of actual engineering. The developed force prediction model for CCS-type disc cutter is a very practical tool for engineers in TBM excavation project.